2011 IEEE Energy Conversion Congress and Exposition 2011
DOI: 10.1109/ecce.2011.6064080
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a 55-kW air-cooled automotive traction drive inverter

Abstract: The purpose of this study is to determine the thermal feasibility of an air-cooled 55-kW power inverter with SiC devices. Air flow rate, ambient air temperature, voltage, and device switching frequency were studied parametrically by performing transient and steady-state simulations. The transient simulations were based on inverter current that represents the US06 supplemental federal test procedure from the US EPA. The results demonstrate the thermal feasibility of using air to cool a cylindrical-shaped 55-kW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Despite the adoption of WBG semiconductors, it remains challenging to design an air-cooled automotive inverter that keeps the overall volume comparable to a liquid cooled one. To determine the feasibility of using forced air to cool an axial flow cylindricalshaped and rectangular-shaped SiC traction drive inverter, Chinthavali et al [43,49] performed a parametric study with various air flow rates, ambient air temperatures, voltages, and device switching frequencies via transient and steady-state simulations. When the inverter was subject to one or multiple current cycles at an ambient temperature of 120 • C, the maximum junction temperature did not exceed 164 and 146 • C at an inlet flow rate of 270 cfm for the cylindrical-shaped and rectangular-shaped inverter, respectively.…”
Section: Forced Air Coolingmentioning
confidence: 99%
“…Despite the adoption of WBG semiconductors, it remains challenging to design an air-cooled automotive inverter that keeps the overall volume comparable to a liquid cooled one. To determine the feasibility of using forced air to cool an axial flow cylindricalshaped and rectangular-shaped SiC traction drive inverter, Chinthavali et al [43,49] performed a parametric study with various air flow rates, ambient air temperatures, voltages, and device switching frequencies via transient and steady-state simulations. When the inverter was subject to one or multiple current cycles at an ambient temperature of 120 • C, the maximum junction temperature did not exceed 164 and 146 • C at an inlet flow rate of 270 cfm for the cylindrical-shaped and rectangular-shaped inverter, respectively.…”
Section: Forced Air Coolingmentioning
confidence: 99%
“…The cooling systems for automotive inverters have adopted numerous different architectures and solutions (Figure 4). Research on gas-cooled inverters, for example, can be found in Chintamani's paper [66]. Nevertheless, two fundamentally different approaches can be considered in inverter cooling: air and liquid cooling.…”
Section: Classification Of Existing Cooling Techniquesmentioning
confidence: 99%
“…Hence, some high ambient temperature converter concepts with SiC have been presented in the literature [16]- [20] and research centers of car manufacturers work on the production of SiC devices [21], [22].…”
mentioning
confidence: 99%